“Buku IPA Berjendela” A Support for Creative Thinking Skill - Sri Yuniyati; Dyah Ayu Fajarianingtyas; Lutfiana Fazat Azizah (Indonesian Journal of Biology Education, 2019)
The availability of teaching materials in SMP and MTs Nurul Muchlishin is limited. Thus, some students need to copy the textbook and simple teaching materials with a percentage of 14% and the students' creative thinking skill is low with a percentage of 48%. An effort that can be done in order to overcome this problem is by developing the teaching materials in the form of Buku IPA Berjendela. The objective of this research is to know the advisability and teacher’s also students’ responses through Buku IPA Berjendela. The type of this research is Research and Development (R & D) and it was developed by using 4D model (Define, Design, Develop, and Disseminate). The result of the study is the advisability of Buku IPA Berjendela on the material content validation is 90.59% (very decent); format validation 94% (very decent); and display validation 94.17% (very decent). Teacher’s response is 100% (very good) and students’ response are 99.56% (very good). Buku IPA Berjendela is suitable to be used to train students' creative thinking skill by using many features in the book.